Sopi in Manggaraian Society: A Gastronomic Studies of Manggaraian Popular Songs - Ans Prawati Yuliantari; Yuliana Jetia Moon (Soshum: Jurnal Sosial dan Humaniora, 2022)
The purpose of this study is to analyze the importance of sopi, a traditional Manggarai drink, in the relationship between individuals and their sociocultural role in Manggarai. The data of this study was taken from two popular Manggarai song texts, Toki Sloki by MukaRakat and Langu, which Embong Lemot created. This article results from a qualitative descriptive study using an anthropological approach. This approach is used to see the role and position of sopi in the relationship between individuals and interpret their sociocultural symbols. Based on the analysis of the text of the two songs, it is known that sopi, as a traditional Manggarai liquor, has a sociocultural position and plays an important role in relationships with others and people who have died. Sopi glues relationships with others in respect, friendship, responsibility, and cooperation. In addition, sopi is also used to commemorate people who have died during traditional ceremonies or in the circle of friends of certain groups.